Development of John Dewey's Theory to Improve Academic Values in a Meaningful Quality of Life for Mahasantri - Najahah, Kamiliya; Isriyah, Mudafiatun (Konseling Edukasi : Journal of Guidance and Counseling, 2025)
Development of John Dewey's Theory to Improve Academic Values in a Meaningful Quality of Life for Mahasantri. Academic grades being one of the important factors in education, students are competing to get the highest score in each circle, and this should be a source of pride. should be a source of pride, but it turns out that this is the gap that is being problem, because students only try to pursue grades without trying to be responsible for them. trying to be responsible for those grades. The purpose of this research and development is to make students educated and qualified as the original purpose of education itself. This development research uses the ADDIE R&D method with 5 important stages in it: Analysis, design, development, implementation and evaluation. This method has been adapted to the objectives needed in the field, with the development of John Dewey's theory used as a reference for solving problems. theory which is used as a reference for solving problems. Research results showed that there was a significant change in the mahasantri's understanding of academics and education from before the intervention and after the intervention. about academics and education from before the intervention and after the intervention. Keywords : Academic; Quality Of Life; John Dewey Theory